Identifying risk factors for placental abruption in subsequent pregnancy without a history of placental abruption. Issue 2 (21st September 2022) - Goldbart, Adi; Pariente, Gali; Sheiner, Eyal; Wainstock, Tamar
Abstract: Objective: To identify first pregnancy risk factors for placental abruption in subsequent pregnancy. Methods: In a population‐based nested case–control study, cases were defined as women with placental abruption in their second pregnancy, and controls as women without abruption. A total of 43 328 women were included in the study, 0.4% ( n = 186) of second pregnancies had placental abruption. Multivariable logistic models were used to study the association between first pregnancy complications and placental abruption in subsequent pregnancy. Results: Having either small for gestational age, preterm delivery, pre‐eclampsia or cesarean delivery during first pregnancy were independently associated with increased risk for placental abruption, and the risk was higher with any additional complication (age adjusted odds ratio [aOR] 2.00, 95% confidence interval [CI] 1.46–2.74; aOR 3.61, 95% CI 2.23–5.86; and aOR 3.86, 95% CI 1.56–9.56, for one, two, and three or more complications, respectively). Conclusion: First pregnancy may serve as a window of opportunity to identify women at risk for future placental abruption. Synopsis: The first pregnancy may serve as a window of opportunity to identify women at risk for future placental abruption.